2020
DOI: 10.1158/1055-9965.epi-20-0723
|View full text |Cite
|
Sign up to set email alerts
|

Automated Quantitative Measures of Terminal Duct Lobular Unit Involution and Breast Cancer Risk

Abstract: Background: Manual qualitative and quantitative measures of terminal duct lobular unit (TDLU) involution were previously reported to be inversely associated with breast cancer risk. We developed and applied a deep learning method to yield quantitative measures of TDLU involution in normal breast tissue. We assessed the associations of these automated measures with breast cancer risk factors and risk. Methods: We obtained eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Gertig et al ( 59 ) and Gabrielson et al ( 68 ) observed more epithelium and less stroma in parous women compared with nulliparous women. Our findings in multiparous women who had a live birth within the last 20 years were similar to other studies that observed less TDLU involution in parous vs nulliparous women ( 30 , 69 ); supported epidemiological reports of increased BC risk in parous women who had a live birth within the last 5 to 24 years compared with nulliparous women ( 70 ); and highlighted the extensive stroma remodeling in mammary glands during pregnancy to accommodate expanding epithelium ( 71 ). The correlation between age of menarche and proportion of stroma reported by us and others ( 59 , 68 ) is in line with a higher percent breast density in young women who had later ages of menarche ( 72 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Gertig et al ( 59 ) and Gabrielson et al ( 68 ) observed more epithelium and less stroma in parous women compared with nulliparous women. Our findings in multiparous women who had a live birth within the last 20 years were similar to other studies that observed less TDLU involution in parous vs nulliparous women ( 30 , 69 ); supported epidemiological reports of increased BC risk in parous women who had a live birth within the last 5 to 24 years compared with nulliparous women ( 70 ); and highlighted the extensive stroma remodeling in mammary glands during pregnancy to accommodate expanding epithelium ( 71 ). The correlation between age of menarche and proportion of stroma reported by us and others ( 59 , 68 ) is in line with a higher percent breast density in young women who had later ages of menarche ( 72 ).…”
Section: Discussionsupporting
confidence: 91%
“…The null associations between age of first birth and length of breastfeeding with breast tissue composition agreed with Gertig et al ( 59 ), whereas Gabrielson et al ( 68 ) found an association between percentage of epithelium and length of breastfeeding, but not percentage of stroma. Using our other method that measures normal TDLUs, we also did not find an association between length of breastfeeding and TDLU involution ( 30 ). Older women have less dense breasts than younger women, with the greatest change in density occurring during the menopause years ( 73 ).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Our group recently developed a novel deep-learning based computational pathology method to capture quantitative measures of breast terminal duct lobular unit (TDLU) involution 22,23 , a purported biomarker of breast cancer. We reported that neither quantitative measures of TDLU involution derived by our technology nor traditional manual qualitative assessment by pathologists was associated with breast cancer among women diagnosed with BBD 24 .…”
Section: Introductionmentioning
confidence: 79%